Here and now or a previously planned strategy? Rethinking the concept of ramification for micro-production in expedient contexts: Implications for Neanderthal socio-economic behaviour. (30th April 2018) - Romagnoli, Francesca; Gómez de Soler, Bruno; Bargalló, Amelia; Chacón, M. Gema; Vaquero, Manuel
Abstract: Ramification is the term used to classify branched productive sequences in which a functional item (the flake) was exploited as a productive item (the core). This technological behaviour was present in Europe and the Levant beginning in the Lower and Early Middle Palaeolithic, but ramified productions were intensely developed in the Late Middle Palaeolithic. Traditionally, ramification has been interpreted as a well-structured behaviour, implying its integration into the provisioning strategies of past humans. This viewpoint has significant implications for the understanding of technological evolution in Neanderthals, suggesting specific cognitive and socio-economic capacities. Ramified procedures were characterised by high flexibility due to the versatile patterns of the core-on-flake and are described in the literature as corresponding to several different knapping concepts and technical procedures. This research aimed to describe the role of ramification in the Late Middle Palaeolithic. We analysed two assemblages from the Abric Romaní site (located in the north-east part of the Iberian Peninsula) characterised by informal, expedient technologies. The focus was on the spatial and temporal fragmentation of the ramified sequences based on the identification of single technical events. The reduction of the scale of analysis and the resulting implementation of temporal resolution of the stone tool assemblages in such expedient contexts allowed us to understand ramification from an innovative perspective, setting aside our bias toward well-defined productive methods associated with preconceived economic and mobility patterns. The results showed that ramification reflected a range of behaviours, implying a variety of planning proficiency, economic strategies and social interactions. This means that 'ramified production' is not meaningful unless is linked with a detailed description of human choices and an understanding of temporal and spatial relationships between knapping events. Furthermore, the results showed that, to approach behavioural issues, we as researchers must change our unitary vision of assemblages and enlarge the scope of categories to which we apply that vision.